High Performance GaSb-Based DBR Laser with On-Chip Integrated Power Amplifier via Gain-Match Design - Juntian Cao; Chengao Yang; Yihang Chen; Hongguang Yu; Jianmei Shi; Haoran Wen; Zhengqi Geng; Zhiyuan Wang; Hao Tan; Yu Zhang; Donghai Wu; Yingqiang Xu; et al. (Applied Sciences)
We reported on a single-longitudinal-mode operated distributed Bragg reflector laser diode emitting at 1950 nm with an on-chip integrated power amplifier. Second-order Chromium–Bragg gratings are carefully designed and fabricated at the end of the ridge waveguide. Achieving a stable single-mode operation with a large injecting current range of 800 mA from 15 °C to 40 °C. The maximum side-mode suppression ratio (SMSR) is up to 42 dB. To increase the output power, an on-chip integrated master oscillator power amplifier (MOPA) is also introduced. MOPA-DBR lasers with different matching configurations between the gain peak and Bragg wavelength are fabricated, resulting in various amplification consequences. The best device is realized with 40 nm red-shifted between Bragg wavelength and photoluminescence (PL) peak. A power amplification of 5.6 times is achieved with the maximum output power of 45 mW. Thus, we put up the feasibility and key design parameters of on-chip integrated power amplification DBR lasers towards mid-infrared.